2016
DOI: 10.1186/s13071-016-1905-7
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the mosquito vector Culex pipiens to the malaria parasite Plasmodium relictum: effect of infected blood intake on immune and antioxidant defences, fecundity and survival

Abstract: BackgroundThe intake of a Plasmodium-infected blood meal may affect mosquito physiology and a series of trade-offs may occur, in particular between immune defences, reproduction and self-maintenance. We evaluated the cost of exposure to Plasmodium in the mosquito vector by investigating the effect of exposure on fecundity and survival and the implication of immune and antioxidant defences in mediating this cost.MethodsWe used the natural Culex pipiens-Plasmodium relictum association. We exposed female mosquito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…In accordance with previous studies in several malaria systems [ 9 , 10 , 15 , 16 ] but see [ 18 ], we observed a negative impact of Plasmodium on mosquito fecundity in the first GC following an infected blood meal. However, the cost payed by infected females was relatively low ( Fig 2 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies in several malaria systems [ 9 , 10 , 15 , 16 ] but see [ 18 ], we observed a negative impact of Plasmodium on mosquito fecundity in the first GC following an infected blood meal. However, the cost payed by infected females was relatively low ( Fig 2 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although the Plasmodium effect on fecundity has been studied in many mosquito/parasite systems [ 9 , 10 , 15 , 16 ], most articles have focused only on the first gonotrophic cycle which is defined as a blood meal followed by an oviposition event [ 6 , 7 , 9 11 , 17 , 18 ]. However, during their lifetime, female mosquitoes take several blood meals, which raises the question of whether they may be able to compensate the fecundity costs induced by an infected blood meal during the following gonotrophic cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Vertebrates can be dead end hosts for Plasmodium parasites if the parasites are not transmitted to a vector in which they undergo their sexual reproduction (Valkiunas 2005 ). The parasite intensity in the blood has been shown to affect life history traits of vectors (Delhaye et al 2016b ) and has been associated to the transmission probability to the vector, measured as oocyst prevalence and oocyst burden (Vezilier et al 2010 ; Pigeault et al 2015 ). It has also been shown that oocyst prevalence and oocyst burden depend on mosquito blood meal size (Pigeault et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using lab-bred Culex pipiens and Plasmodium relictum, infection was shown to decrease mosquito fecundity (Vézilier et al, 2012;Pigeault and Villa, 2018) and to increase their survival under ad libitum food conditions (Vézilier et al, 2012). On the opposite, using mosquitoes reared from egg rafts collected in the field, the same infection was shown to slightly increase fecundity (Delhaye et al, 2016) and to decrease survival under a food restriction regime (Lalubin et al, 2014). Independently of the systems used, most of these studies did not find an effect of the infection on host longevity when food was given ad libitum (Lalubin et al, 2014;Delhaye et al, 2016;Pigeault and Villa, 2018).…”
Section: Natural Versus Experimental Infectionsmentioning
confidence: 99%
“…On the opposite, using mosquitoes reared from egg rafts collected in the field, the same infection was shown to slightly increase fecundity (Delhaye et al, 2016) and to decrease survival under a food restriction regime (Lalubin et al, 2014). Independently of the systems used, most of these studies did not find an effect of the infection on host longevity when food was given ad libitum (Lalubin et al, 2014;Delhaye et al, 2016;Pigeault and Villa, 2018). Moreover, Plasmodium falciparum increases fecundity and do not reduce survival in Anopheles gambiae (Alout et al, 2016).…”
Section: Natural Versus Experimental Infectionsmentioning
confidence: 99%